Succession Challenges in Small-Medium Outboard Marine Businesses of Malaysian Chinese Family Ownership. - Kuong, Tang Kie (2018)
This research study focuses on the succession challenges in small-medium outboard marine businesses of Malaysian Chinese family ownership. The founder-owners face challenges in convincing the next generation members to establish their careers within the family business and to ensure successions are in place to safeguard the family’s wealth. A gap exists in the research literatures concerning such family business owners; and their experiences would provide valuable information to other Malaysian Chinese family businesses planning to start the succession journey. An exploratory case study methodology to research five Malaysian Chinese family businesses cases in Klang Valley, Selangor, Malaysia is used in this study. The primary qualitative data were obtained through in-depth, semi-structured interviews and observations. The research data lead to the identification of the following themes: generational change affects the survival of small-medium Malaysian Chinese family-owned businesses; the founder-owners’ intention and desire for business to pass to the next generation give rise to the imperative of succession; the founder-owners’ motive and goals, family context and the business nature would determine a large part to how the succession plans are carried out and the upbringing, expectation and obligations would determine how the next generations of children would view the prospect of taking over the family business. From this, a succession model that detailed an inclusive approach to succession planning process between the two generations is established. This research study could also facilitate other Malaysian family businesses to rethink and refocus on the importance of undertaking an inclusive approach to succession planning. The success of family-owned Small-Medium Enterprises (SMEs) would justify the Malaysian Government’s continual efforts to support their growth.